Coleoptera of the Penza region, Russia based on fermental crown trap - Alexander Ruchin; L.V. EGOROV; O.A. POLUMORDVINOV (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ruchin AB, Egorov LV, Polumordvinov OA. 2021. Coleoptera of the Penza region, Russia based on fermental crown trap). Biodiversitas 22: 1946-1960. There are the results of processing the material of the 2019-2020 studies on Coleoptera from the Penza region, Russia. The surveys were carried out using fermental crown traps in various habitats on the territory of 18 districts of the region. In total, 18 traps were installed in 2019 and 96 traps – in 2020. During the research, 5,577 specimens were collected and recorded. Ninety-seven species from 19 families were found, of which 43 species are new to the Penza region. The most diverse families are Cerambycidae (24 species) and Elateridae (11 species). Species from the families Nitidulidae (3281 specimens), Scarabaeidae (1497 specimens), and Cerambycidae (453 specimens) predominated in the traps. A list of species is given, indicating references and information on biology. New data is given for 4 species included in the Red Data Book of the region (Protaetia fieberi, Protaetia speciosissima, Gnorimus variabilis, Purpuricenus globulicollis).